ALTERNATIF INOVASI MUTUAL, MELALUI PELATIHAN DAN PENGEMBANGAN UNTUK MENGHASILKAN PRODUK KREATIF, PENINGKATAN PENGHASILAN (INCOME GENERATION) DALAM MENDUKUNG CREATIVE INDUSTRY - Widayati Widayati Christiana (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2010)
Demand of woven bamboo handicraft in big cities, especially in Surabaya, increases from time to time. At the same time, based on the researcher’s observation over some years on woven bamboo cluster at Kemiren village, Banyuwangi regency, East Java, the cluster tends to have undergone insignificant development and innovation. The home industries are usually run by low-income families and produce the products like capil (sun hat) and ilir (traditional tool to cool the heat by wagging it). The producers have little knowledge about product innovation so that they can take part in the market competition. Therefore, to improve the quality as well as the variety of the products so that producers are able to increase their income, some measures need to be taken through training programs on the field of creative arts. In this research, the writer uses a qualitative, descriptive method. The result shows that: 1) the producers were enthusiastic and actively participated in the program; 2) they initiated and established an association of woven bamboo handicraft producers;and 3) they were able to create a sample product as exemplified by instructors but the quality has yet to be improved. For this purpose, further trainings should be conducted on regular basis.